Gambaran Pola Asuh Gizi Balita di Kampung Tomolol Kecamatan Misool Timur Kabupaten Raja Ampat - Mjam, Bertha; Mautang, Theo W.E; Mokoagow, Anuardin (Jurnal Lentera Sehat Indonesia, 2025)
Toddlerhood is a critical period in a child's physical and mental development. Parenting and balanced nutrition are key factors influencing the quality of a child's growth and development. This study aims to describe the nutritional parenting patterns of toddlers in Tomolol Village, East Misool District, Raja Ampat Regency. This study used a descriptive research method to provide an overview of toddler nutritional parenting patterns. The results showed that the majority of respondents (45 respondents) had good knowledge, 69.2% of whom were aged 21-34, 41 (63.1%), 29 (44.6%), and 36 (55.4%) were housewives. Regarding the level of knowledge of toddler nutritional parenting patterns in Tomolol Village, 45 (69.2%) had good knowledge, 12 (18.5%) had sufficient knowledge, and 8 (12.5%) had insufficient knowledge.